Isolation of the causal virus of infectious salmon anaemia (ISA) in a long-term cell line from Atlantic salmon head kidney - Dannevig, B H; Falk, K; Namork, E (Journal of general virology, 1995)
A long-term cell line (SHK-1) supporting replication of the causal virus of infectious salmon anaemia (ISA) has been established. The cell line was developed from a culture of Atlantic salmon (Salmo salar L.) head kidney cells. CPE was observed in SHK-1 cells 12-14 days after inoculation with ISA-infective tissue material. The time for CPE to develop decreased after repeated passages of medium from infected cell cultures to new cultures. Transmission trials demonstrated that Atlantic salmon parr developed ISA after intraperitoneal injection of preparations made from infected cells and growth medium. The ISA infectivity of the cell preparations increased with incubation time of inoculated cells. Cell cultures in a second passage were found to have a higher infectivity than the primary inoculated cultures. Virus particles with a diameter of approximately 100-120 nm, and which contained an external envelope and granules were seen in electron micrographs of thin sections of infected cells. Most of the virus particles were located extracellularly close to the cell surface, and in some cases, a connection between virus and plasma membrane could be observed. This indicates that virus particles were released by budding. Enveloped virus particles of 45-140 nm in diameter were seen in abundance in electron micrographs of a negatively stained purified virus preparation. Large, highly pleomorphic particles up to 700 nm in the longest dimension were occasionally observed in unpurified preparations. The evidence is therefore strong that the virus isolated in SHK-1 cells is the aetiological agent of ISA.